3xy
<span>y(3y)/3xy + y(xy)/3xy + (y+1)(3x)/3xy </span>
<span>NOW since all of the fractions have a denominator of 3xy, drop the denominators and solve using the numerators. </span>
<span>y(3y) + y(xy) + (y+1)(3x) </span>
<span>3y^2 + xy^2 + 3xy +3x </span>
<span>cannot simplify further.</span>
Answer:
110
Step-by-step explanation:
5.5 x 20 = 110
Answer:
(1 cm)cos3πt
Step-by-step explanation:
Since the piston starts at its maximal height and returns to its maximal height three times evert 2 seconds, it is modelled by a cosine functions, since a cosine function starts at its maximum point. So, its height h = Acos2πft
where A = amplitude of the oscillation and f = frequency of oscillation and t = time of propagation of oscillation.
Now, since the piston rises in such a way that it returns to the maximal height three times every two seconds, its frequency, f = number of oscillations/time taken for oscillation where number of oscillations = 3 and time taken for oscillations = 2 s
So, f = 3/2 s =1.5 /s = 1.5 Hz
Also, since the the piston moves between 3 cm and 5 cm, the distance between its maximum displacement(crest) of 5 cm and minimum displacement(trough) of 3 cm is H = 5 cm - 3 cm = 2 cm. So its amplitude, A = H/2 = 2 cm/2 = 1 cm
h = Acos2πft
= (1 cm)cos2π(1.5Hz)t
= (1 cm)cos3πt
Answer:
(7,2)
Step-by-step explanation:
x + y = 9 + 2x - 3y = 8 is really two equations, and you should show this by separating x + y = 9 from 2x - 3y = 8 through the use of a comma, or the word "and," or through writing only one equation per line.
Here you have the system of linear equations
x + y = 9
2x - 3y = 8.
Let's solve this system by elimination. Mult. the 1st eqn by 3, obtaining the system
3x + 3y = 27
2x - 3y = 8
-------------------
5x = 35, so that x = 7. Subbing 7 for x in x + y = 9, we get 7 + y = 9, indicating that y = 2.
Thus, the solution to this system of equations is (7,2).
Answer:
42
Step-by-step explanation:
First I'm going to assume that C and A are perpendicular.
Because its perpendicular, this creates a 90 degree angle which can be used to create the following equation.
![90 = 6x - 6 + 5x + 8](https://tex.z-dn.net/?f=90%20%3D%206x%20-%206%20%2B%205x%20%2B%208)
Reduce
11x = 88
x = 8
We then plug in 8 into the equation 6x - 6 in order to solve for that angle.
6(8) - 6
42